RİBBON ÇATIYA GÖRE MANYETİK EĞRİLER - ANIL, BARAN (Fırat Üniveristesi, 2021)
Öklid uzayında eğriler teorisinde farklı çatılara göre birçok çalışma yapılmıştır. Birçok bilim adamı bu teoride Frenet çatı, Bishop çatı, Adapted çatı, Ribbon çatı gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu çalışmada, 3-boyutlu Öklid uzayında Ribbon çatıya göre manyetik eğriler incelenmiştir. Bu çatıya göre f-manyetik eğriler ve g-manyetik eğrileri verilmiştir

Many studies have been done according to different frames of the theory of curves in Euclidean Space. Many scientists have studied frames such as Frenet frame, Bishop frame, Adapted frame, Ribbon Frame in this theory. These frames help us in the characterization of curves. In this study, magnetic curves according to Ribbon frame in 3-dimensional Euclidean space are investigated. f-magnetic curves and g-magnetic curves according to this frame are given.
Magnetic curves according to the ribbon frame
Keywords: Matematik